2017
DOI: 10.1116/1.4978892
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of single-phase SnS film by H2 annealing of amorphous SnSx prepared by atomic layer deposition

Abstract: This study evaluated a simple and novel route to fabricate single-phase SnS thin films, consisting of the growth of smooth amorphous SnS2 films by atomic layer deposition at very low temperature using tetrakis(dimethylamino)tin {TDMASn, [(CH3)2N]4Sn} and hydrogen sulfide followed by H2 annealing at controlled higher temperatures. The properties of the SnS films fabricated by subjecting the amorphous as-grown SnS2 films deposited at 100 °C to post-H2 annealing at 360 °C were superior to those of the as-grown Sn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 34 publications
0
20
0
Order By: Relevance
“…The interlayer spacing (d-spacing) of SnS grown at 180 and 160 °C corresponding to the strongest XRD peak at 2θ = 31.8 and 15.7°, is found to be 0.28 and 0.59 nm respectively. Previous studies 35 have also demonstrated that SnS film is predominantly formed above 180 °C, whereas the single phase of SnS 2 film is formed at a slightly lower deposition temperature of 160 °C. These findings suggest that the formation of SnS is more favourable at high temperatures, as compared to relatively low temperatures.…”
Section: Resultsmentioning
confidence: 79%
See 3 more Smart Citations
“…The interlayer spacing (d-spacing) of SnS grown at 180 and 160 °C corresponding to the strongest XRD peak at 2θ = 31.8 and 15.7°, is found to be 0.28 and 0.59 nm respectively. Previous studies 35 have also demonstrated that SnS film is predominantly formed above 180 °C, whereas the single phase of SnS 2 film is formed at a slightly lower deposition temperature of 160 °C. These findings suggest that the formation of SnS is more favourable at high temperatures, as compared to relatively low temperatures.…”
Section: Resultsmentioning
confidence: 79%
“…The first Raman peak at 56 ± 2 cm −1 [B 2g (LO)-A g (TO)] and last peak at approximately 313.4 cm −1 [A g (TO) + A g (LO2)], can be assigned to the second order multiple phonons scattering process. In addition, the observed Raman active peak at 56 ± 2 cm −1 belongs to the vibrational mode of SnS phase, whereas the specific Raman peak at 313.4 cm −1 (only can be seen in the SnS x -160 sample) is associated with optical phonon mode of 2H-SnS 2 poly-type with a hexagonal symmetry, and is related to Sn-S bonding in the a-c plane 18,35 . Moreover, the Raman spectra obtained from SnS x @NF (Fig.…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…43 Another example is the production of 2D SnS, in which SnS 2 is deposited first via ALD and then reduced in H 2 into 2D SnS at high temperature. 44 This R3 route has also been used for h-BN, where a polymer was first deposited via ALD at low temperature and then converted into h-BN in NH 3 at high temperature. 45,46 This route has multiple benefits: (1) ease of generalization for more 2D materials;…”
Section: Ald Fundamentals and Strategies For 2d Materialsmentioning
confidence: 99%